2024
DOI: 10.1002/ase.2424
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of plastinated specimens in anatomy education: A systematic review and meta‐analysis

Julian Shu Kai Goh,
Ramya Chandrasekaran,
Srinivasa Rao Sirasanagandla
et al.

Abstract: Plastination, a permanent preservation method for human tissues and organs, is increasingly being used in anatomy education. However, there is a paucity of systematic reviews and meta‐analyses summarizing the educational efficacy of plastinated specimens. This meta‐analysis compared the assessment scores of students exposed to plastinated specimens against those exposed to other common instructional methods. A systematic search was conducted through four databases, from 2000 to July 2022. Titles and abstracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Previous studies have reported the application of the ADDIE model to anatomy education, but there is a paucity of research on detailed digital anatomy curricula. In addition, several meta-analyses have shown no statistical difference in student performance scores when comparing traditional anatomy to other anatomy resources 37 , 38 . This highlights that pedagogical goals and methods of application may have a greater impact on student learning outcomes than the inherent characteristics of the teaching method.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the application of the ADDIE model to anatomy education, but there is a paucity of research on detailed digital anatomy curricula. In addition, several meta-analyses have shown no statistical difference in student performance scores when comparing traditional anatomy to other anatomy resources 37 , 38 . This highlights that pedagogical goals and methods of application may have a greater impact on student learning outcomes than the inherent characteristics of the teaching method.…”
Section: Discussionmentioning
confidence: 99%